Sparkle of existential time as a sanctuary in marital counselling - Kalantarkousheh, Seyed Mohammad; Hassan, Siti Aishah; Abdul Kadir, Rusnani; Abu Talib, Mansor (Marsland Press, 2011)
Nowadays, Existential thought is considered to be a practical approach among psychologists and counsellors. Nevertheless, what seems to be ignored is paying thoughtful attention to all dimensions of Existential thought which is an essential matter among counsellors and psychologists. Moreover, some issues in Existential thought such as time are disregarded among marital counsellors as well as individual counsellors. The goal of this article is to allocate exhausting existential time to benefit marital counsellors. Findings show that existential time has full potential to be applied for marital counselling. Furthermore, review of the related literature demonstrates that there is not enough experimental and descriptive research to evaluate the effect of existential time on matrimony.